THE IMPLICATION OF SYMBOLIC VIOLENCE CULTURE TO INTROVERTED STUDENTS OF BALI UNIVERSITIES ON THE EDUCATIONAL PROCESS - Desi Wulandari, Ni Putu; Ardhana, I Ketut; Pageh, I Made; Arjani, Ni Luh (E-Journal of Cultural Studies, 2021)
This article is aimed at describing the implications of symbolic violence towards introvert students in English education departments of universities in Bali on the educational process. There were three universities to be decided as the setting of this research; (1) Mahasaraswati University Denpasar, (2) Ganesha University of Education Singaraja and (3) IKIP Saraswati Tabanan. The subject of this study was the introvert students and distinctive lecturers of those three English education departments. The result of this study reveals that the implication on process can be perceived through class’ behavioral management, classroom learning management and classroom physical space management. Those kinds of managements were applied reversely from the critical pedagogy and emancipatory learning idealism that leads to symbolic violence, especially to the introvert students. The application was not considering the personality uniqueness of introverted students and created a one-size-fits-all idealism by adopting extroverted idealism and force introverted students to fit in it. Key words : symbolic violence, introvert, English education, critical pedagogy